2020
DOI: 10.4244/aij-d-19-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcatheter aortic valve size on leaflet stresses: implications for durability and optimal grey zone sizing

Abstract: Aims: As indications for transcatheter aortic valve replacement (TAVR) continue to expand towards younger and lower-risk patients, durability becomes an increasingly important question. Durability decreases as leaflet stresses increase, but the impact of transcatheter heart valve (THV) size on stress is unknown. Patient annulus sizes can fall within "grey zones" between 2 TAVR sizes. Our aim was to examine the impact of balloon-expandable THV size on leaflet stresses.Methods and results: SAPIEN XT 23 mm, 26 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hereby, based on the results of our study and very limited previous data about borderline annulus patients, it does not seem possible to make certain recommendations regarding valve selection and procedural steps. For BE valves although the undersizing but overfilling strategy sounds like a reasonable strategy in most cases, the study by Xuan et al 25 has conflicting results to make such a recommendation. As a matter of fact, SE valves do not have such an option as underfilling or overfilling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereby, based on the results of our study and very limited previous data about borderline annulus patients, it does not seem possible to make certain recommendations regarding valve selection and procedural steps. For BE valves although the undersizing but overfilling strategy sounds like a reasonable strategy in most cases, the study by Xuan et al 25 has conflicting results to make such a recommendation. As a matter of fact, SE valves do not have such an option as underfilling or overfilling.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this study, undersizing but overfilling was related to decreased PVL and mean postprocedural transvalvular pressure gradient and reduced incidence of annular rupture. Conversely, Xuan et al 25 evaluated the impact of THV size on leaflet stress in patients with grey zone annulus and implanted ESXT valves. Leaflet stress is considered to be related to accelerated valve degeneration and shorter durability according to the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Second, true valve size in patient 2 can only be approximately determined because measurements by expert group are between 2 TAVR sizes. Besides the fact that correct measurement between 2 TAVR sizes is subject of current research [ 32 ], a ICC of 0.981 is considered as an excellent degree of interrater reliability [ 33 ]. Third, the training-free interval between T1 and T2 differed in the minimum and in the maximum (minimum 13 days, maximum 22 days).…”
Section: Discussionmentioning
confidence: 99%
“…Flameng et al followed 664 SAVR patients for a median of 6.1 years and showed that PPM was independently associated with a 2.3-fold increase in the risk of SVD (35). This association may be related to higher mechanical leaflet stress in the setting of high flow rates and higher mechanical leaflet stress related to under-expansion of the valve (46)(47)(48).…”
Section: Ppm and Valve Durabilitymentioning
confidence: 99%